2016
DOI: 10.4238/gmr.15038715
|View full text |Cite
|
Sign up to set email alerts
|

Association between the CDH1-472delA and -160C>A polymorphisms and diffuse and intestinal gastric cancer in a Mexican population

Abstract: ABSTRACT. Gastric cancer (GC), the third leading cause of cancerrelated deaths in Mexico and worldwide, can be classified into diffuse (DGC) or intestinal (IGC) types based on its histological characteristics. DGC is characterized by reduced expression of the cell adhesion protein E-cadherin, which is encoded by CDH1. The -472delA (rs5030625) and -160C>A (rs16260) polymorphisms in CDH1 induce a decrease in gene transcription; in fact, these mutated alleles have been associated with GC in some populations, with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…An important aspect to consider is that, with the exception of variant -285C > A (or -160C > A) [21], no other variants have been described for the Mexican population. It would be important to investigate the frequencies of the variants described in this population (Additional file 4).…”
Section: Discussionmentioning
confidence: 99%
“…An important aspect to consider is that, with the exception of variant -285C > A (or -160C > A) [21], no other variants have been described for the Mexican population. It would be important to investigate the frequencies of the variants described in this population (Additional file 4).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the normal C and variant A allele frequencies in CDH1 gene were found to be 69.0% and 31.0% in cases. On the other hand, frequency of variant A allele was found to be 16.6% in Han Chinese population for pancreatic cancer, 45 15.9% and 20.0% in Chinese population for gastric and esophageal cancer, 44 17.0% in Mexico for gastric cancer, 42 and 34.2% in India for breast cancer. 67 For Exo1 (K589E) gene, variant A allele frequency in our study group was found to be 35.0%, whereas in other studies carried out in China and Taiwan, the frequencies were 24.3%, 21.0%, 22.8%, and 25.0% for gastric, 36 breast, 37 lung, 38 and cervical cancer, 75 respectively.…”
Section: Discussionmentioning
confidence: 95%
“…High consumption of SFA and MUFA has been associated with increased risk, whereas PUFA intake reduced (70-80%) that risk of gastric cancer in Mexico (López-Carrillo et al, 1999;Sampieri and Mora, 2014). The main sources of PUFA in the Mexican diet are sunflower and safflower oils; therefore increased use of our high linoleic safflower oil (75-86% PUFA, 10-23 PUFA/SFA ratio) can be effective in greatly reducing the risk of gastric cancer, the third leading cause of cancer related deaths in Mexico (Bustos-Carpinteyro et al, 2016). Furthermore, the antioxidant components of safflower oil, particularly the phenolics may also play an important etiological role in reducing the risk of chronic diseases and attenuating inflammation, the major risk factor for metabolic diseases.…”
Section: Resultsmentioning
confidence: 99%